2020
DOI: 10.1007/s13187-020-01704-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness to Implement Physical Activity and Rehabilitation Guidelines in Routine Primary Care Cancer Rehabilitation: Focus Group Interviews Exploring Rehabilitation Professionals’ Perceptions

Abstract: To explore primary care professionals' perceptions of physical activity and other cancer rehabilitation practice in cancer survivors, investigating the preparedness to implement guidelines regarding cancer rehabilitation. We collected qualitative data through seven semi-structured focus group interviews with 48 rehabilitation professionals, with mean 9 years of experience in primary care rehabilitation (32 physiotherapists, 15 occupational therapists, and 1 rehabilitation assistant) in a primary care setting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, the specific content and methods of rehabilitation interventions, such as how often, how long, and what kind of rehabilitation should be performed for these patients, are poorly documented. Therefore, rehabilitation therapists currently deliver treatment to patients based on their own experiences; this may cause differences in the quality of rehabilitation provided [26,27]. In addition, as many cancer patients become increasingly frail in the terminal phase [1,25], routine interventions might be harmful.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the specific content and methods of rehabilitation interventions, such as how often, how long, and what kind of rehabilitation should be performed for these patients, are poorly documented. Therefore, rehabilitation therapists currently deliver treatment to patients based on their own experiences; this may cause differences in the quality of rehabilitation provided [26,27]. In addition, as many cancer patients become increasingly frail in the terminal phase [1,25], routine interventions might be harmful.…”
Section: Introductionmentioning
confidence: 99%
“…Primary care physicians frequently cite a lack of knowledge and training as a barrier to the promotion of PA 15–18,20–25,28–30,40–48 . A nationwide survey of 1013 GPs in England reported that only 20% were broadly familiar with the national PA guidelines, and 55% reported they had not undertaken any training in PA counselling or advice 9 .…”
Section: Methodsmentioning
confidence: 99%
“…Primary care physicians frequently cite a lack of knowledge and training as a barrier to the promotion of PA. [15][16][17][18][20][21][22][23][24][25][28][29][30][40][41][42][43][44][45][46][47][48] A nationwide survey of 1013 GPs in England reported that only 20% were broadly familiar with the national PA guidelines, and 55% reported they had not undertaken any training in PA counselling or advice. 9 A failure of medical school education in the United Kingdom was suggested by Weiler et al 49 in a review of medical school curricula.…”
Section: Knowledge/skillsmentioning
confidence: 99%
“…According to the law, it is recommended that cancer rehabilitation takes place in survivors’ local community. However, programs in primary healthcare are criticized for being random, fragmented, not research based, and focusing on single components, and survivors are often left to find such programs on their own 34–36 . This highlights the need to develop and pilot evidence-based cancer rehabilitation programs in primary healthcare 37–40 .…”
Section: Introductionmentioning
confidence: 99%
“…However, programs in primary healthcare are criticized for being random, fragmented, not research based, and focusing on single components, and survivors are often left to find such programs on their own. [34][35][36] This highlights the need to develop and pilot evidence-based cancer rehabilitation programs in primary healthcare. [37][38][39][40] Most of the research on cancer rehabilitation is conducted on residential rehabilitation programs at specialist healthcare level, and it may seem apparent that multidimensional rehabilitation programs in primary healthcare should be built on the same principles.…”
Section: Introductionmentioning
confidence: 99%